Understanding Lecturer Performance Behavior: A Systematic Literature Review on the Role of Work Environment and Motivation - Puput Puspito Rini; Sudadio Sudadio; Asep Muhyidin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Lecturer performance behavior plays a crucial role in enhancing the quality and effectiveness of higher education. While the work environment and motivation have been recognized as key influencing factors, their interactive effects remain underexplored in the literature. This study conducted a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework, analyzing 75 peer-reviewed publications from 2015 to 2024. The literature was sourced from major academic databases including Scopus, Web of Science, Google Scholar, and the Indonesian national journal portal (Garuda). Inclusion criteria focused on studies examining lecturer performance behavior in relation to work environment and motivation within higher education contexts. Thematic synthesis revealed two dominant and interrelated factors: (1) the work environment—encompassing academic leadership, institutional support, organizational culture, and infrastructure; and (2) motivation—comprising intrinsic and extrinsic elements. Studies showed that lecturer performance is significantly enhanced when a supportive environment aligns with strong motivational drivers. Conversely, high motivation alone or favorable environments without corresponding motivation often yield limited impact. The findings suggest that lecturer performance behavior is shaped by the dynamic interaction between institutional conditions and motivational mechanisms. This review contributes a more integrative conceptual framework by moving beyond fragmented approaches, highlighting the need for holistic academic human resource strategies. Future research should adopt longitudinal and mixed-methods designs to capture the evolving nature of this interaction over time.